Exploring the effect of the pro-inflammatory microenvironment on the expression of the tumor-related RAC1B splice variant in colorectal cancer cells - Bessa, Cláudia (2022)
An inflammatory tumor cell microenvironment has been identified as a critical tumor-promoting condition providing survival signals to which cancer cells respond with changes in their gene expression. Interestingly, alternative splicing (AS) is one key gene regulatory mechanism that responds to extracellular signals directly affecting cancer progression. For example RACB1, a RAC1 AS variant, previously identified by our group in a subset of BRAF-mutated colorectal tumors [3], was found increased in colon mucosa under inflammatory conditions, both in samples from inflammatory bowel disease patients or following experimentally-induced acute colitis in a mouse model. Based on these findings, the main goal of this work was to determine which pro-inflammatory signals from stromal cells lead to an increase in RAC1B expression levels in colorectal cancer (CRC) cells. For that, we use a more physiologically relevant culture model consisting of a 2D polarized monolayer of Caco-2 CRC cells grown on porous membranes, and then co-cultured with stromal cells, including fibroblasts, monocytes and macrophages. RAC1B expression was analyzed in Caco-2 cells by RT-qPCR, Western blot and confocal fluorescence microscopy. In fact, co-culture experiments revealed that the combined presence of fibroblasts and/or M1 macrophages induced a transient increase in RAC1B mRNA and protein levels in Caco-2 cells, accompanied by a loss of epithelial organization. Besides RAC1B, a panel of 6 additional pairs of tumor-related AS variants was analyzed, being observed an alteration of the expression ratios in 3 out of the 6 variants tested. Moreover, using a human inflammation array, we were able to identify from the conditioned co-culture media three cytokines that associated with increased RAC1B: IL-1, IL-6 and IL-8. Remarkably, the incubation of polarized Caco-2 cells with described purified cytokines was sufficient per se to trigger an increase in RAC1B expression in a dose-dependent manner. As a whole, our data indicate that pro-inflammatory signals can modulate AS in colon epithelial cells, particularly leading to an increase in RAC1B levels. Future identification of the interleukin-regulated signaling pathways involved in altered AS should provide details on how these talk to the splicing machinery, and may represent a promising approach to discovery novel therapeutic targets for suppressing oncogenic splice variants.